EFFECT OF CIRCADIAN RHYTHM ON THE BLOOD PRESSURE ADJUSTMENT IN RESPONSE TO A PHYSICAL STRESS - Aftab, Muhammad Tariq; Miraj, Nimrah; Masood, Sobia; Shamim, Sehba; Fayyaz, Shafaq (Pakistan Journal of Physiology, 2013)
Background: Many studies have shown a relationship between circadian rhythm and certain physiological functions and pathological changes in the body. Blood pressure is highly sensitive in this regard. The role of circadian rhythm in controlling the blood pressure requires further exploration. This study was conducted to investigate variability of blood pressure adjustment due to circadian rhythm after a physical stress. Method: Data was collected from 29 undergraduate students after consent and briefing them the nature and purpose of the study. Blood pressure changes in the morning and afternoon after same physical stress were noted. Result: It was found that circadian rhythm has significant effect (p<0.05) on systolic and diastolic blood pressures in the morning (from 8 to 9 AM) and afternoon (from 2 to 3 PM). This difference becomes insignificant (p>0.05) in these two phases of the day due to larger changes (p<0.05) in these two parameters by same exercise. But after five minutes the adjustment of systolic and diastolic Blood pressures in so effective that a significant (p<0.05) difference is again retained in the systolic and diastolic blood pressures. Conclusion: The blood pressure controlling mechanism becomes more responsive with circadian rhythm to control the larger changes of blood pressure effectively.